Comparing high-income and low- and middle-income country host perspectives on students' short-term experiences in global health: a qualitative analysis. (March 2018) - Myser, Catherine; Astle, Barbara; Cherniak, W; Latham, Emily; Anguyo, Geoffrey; Beaunoir, Tessa; Buenaventura, Joel H; DeCamp, Matthew; Diaz, Karla; Eichbaum, Quentin; Hedimbi, Marius; Nwobu, Charles; et al.
Abstract: Background: Thousands of students travel yearly from high-income countries (HICs) to low-income and middle-income countries (LMICs) for short-term experiences in global health, with much less travel by LMIC students to HICs. Little structured research has been done to seek host perspectives, particularly from LMICs, on what they would like to teach learners. By seeking LMIC host perspectives, we aimed to improve global health pedagogy, curriculum design, assessment, and experiential learning, better meeting host goals and expectations. Our additional aim was to improve mutual respect and trust, share power honestly and ethically, and facilitate more genuinely collaborative agenda setting between LMIC and HIC partners. Methods: We previously did a hybrid quantitative and qualitative web-based survey from Sept 1, 2015, to Dec 31, 2015, exploring global health competencies with particular attention to LMIC hosts supervising and housing trainees in short-term experiences in global health. 274 host perspectives were gleaned from 38 countries speaking 22 languages. In this qualitative study, we analysed open-ended questions and responses not previously covered from the same survey data. 97 of 274 responses were selected for qualitative analysis, conducted via content analysis and coding, ensuring inter-rater reliability, and comparing HIC and LMIC responses. Findings: Four core themes emerged in our content analysis regarding desired global health core competencies: most important global health core competencies; biggest mistakes students make; biggest challenges students face; and what students should remember most in experiential global health education. Interpretation: Our qualitative study revealed intriguing comparative results addressing core controversies in global health, such as who "does global health" and where one must be to "do global health". Moving forward we hope this initial survey research will facilitate more genuinely collaborative agenda setting between North–South and East–West partners. Funding: Child Family Health International.